QUBIC I: Overview and Science Program - Hamilton, J. Ch.; Mousset, L.; Battistelli, E.S.; De Bernardis, P.; Bigot Sazy, M. A.; Chanial, P.; Charlassier, R.; D'Alessandro, G.; De Petris, M.; Gamboa Lerena, Martín Miguel; Grandsire, L.; Landau, Susana Judith; et al. (IOP Publishing, 2021)
Fil: Hamilton, J. Ch.. Université de Paris; Francia. Centre National de la Recherche Scientifique; Francia